The Impact of Local Own-Source Revenue and Balancing Funds on Regional Expenditure in Gorontalo Province: A Study from 2019-2024 - Ntou, Siti Nur Aulia Ramadhani; Blongkod, Harun; Husain, Siti Pratiwi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the effect of Local Own-Source Revenue (Pendapatan Asli Daerah or PAD) and Balancing Funds (Dana Perimbangan) on Regional Expenditure (Belanja Daerah) of district and city governments in Gorontalo Province during the 2019–2024 period. The research employs a quantitative approach using secondary data obtained from the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia. The analytical method used is multiple linear regression with the assistance of IBM SPSS version 16. The findings reveal that Local Own-Source Revenue (PAD) has a positive and significant effect on Regional Expenditure. This indicates that an increase in PAD enhances the local government’s ability to finance public spending, reflecting stronger fiscal capacity and improved regional financial independence. Similarly, Balancing Funds (Dana Perimbangan) also show a positive and significant influence on Regional Expenditure, suggesting that fiscal transfers from the central government remain a crucial source of funding for regional development programs. The simultaneous test results further confirm that both PAD and Balancing Funds jointly have a positive and significant impact on regional spending across districts and cities in Gorontalo Province. The coefficient of determination (R²) indicates that these two independent variables explain a substantial portion of the variation in regional expenditure, while the remaining variation is influenced by other factors not included in the model. These results highlight the continuing reliance of local governments on central government transfers while emphasizing the strategic importance of increasing PAD to achieve greater fiscal autonomy. Overall, this study underscores the need for local governments in Gorontalo Province to optimize their revenue-generating potential through improved tax collection, better management of local assets, and expanded economic activities. Strengthening PAD will not only reduce dependency on Balancing Funds but also contribute to more sustainable and independent regional fiscal management.